2000
DOI: 10.1106/x80m-4uef-cppk-m15e
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Matrix Woven Fabric Composites Subjected to Low Velocity Impact: Part I-Damage Initiation Studies

Abstract: An investigation was undertaken to study the damage initiation behavior in polymer matrix laminated composite plates subjected to a transverse central low velocity point impact load. Inplane failure of the layers in the form of matrix cracking/lamina splitting and delaminations were the primary objectives of the study. The study has been carried out using modified Hertz contact law and an inhouse three-dimensional transient finite element analysis (FEA) code. The inplane failure functions and the interlaminar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…Material of the plate and the impactor was steel. The results obtained for contact force history and displacement history for the plate and the impactor by the present inhouse FEA code and that obtained by Karas were compared, and a very good correlation was obtained [12,13,17,18].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Material of the plate and the impactor was steel. The results obtained for contact force history and displacement history for the plate and the impactor by the present inhouse FEA code and that obtained by Karas were compared, and a very good correlation was obtained [12,13,17,18].…”
Section: Resultsmentioning
confidence: 82%
“…For this, an interlaminar failure function based on through-the-thickness quadratic failure criterion as proposed by Brewer-Lagace has been used [18,21]. An interlaminar failure function, I is defined as follows: Here, σ 3 , τ 23 and τ 31 are the induced stress components and Z, S 23 and S 31 are the corresponding strength values.…”
Section: Interlaminar Failure Function Plotsmentioning
confidence: 99%
“…They found improvements in the load carrying capability of hybrid composites as compared with carbon/epoxy laminates with slight reduction in stiffness and enhancement in damage tolerance of structures by hybridization. Naik et al [8,9] have published various works on the impact of polymer matrix woven fiber composites, reporting that the maximum displacement and duration of impact decreases with increase in in-plane modulus of elasticity. They also reported that the delamination mode is the first possible mode of failure, and that failure is often initiated at the top interface [7] .…”
Section: Introductionmentioning
confidence: 98%
“…Most of the previous impact studies have focused on single low-velocity and repeated impact at room temperature. Naik et al (2000) investigated the damage imparted to woven-fabric and cross-ply E-glass/epoxy and carbon/epoxy laminates under low-velocity (1 and 3 m/s) impact. They reported that woven-fabric laminates were more resistant to in-plane impact damage than cross-ply lamiates.…”
Section: Introductionmentioning
confidence: 99%